A basic study on measurement of experience using an unconscious response to the artificially created visual environment - Murai, K.; Hayashi, Y.; Inokuchi, S. (IEEE International Conference on Systems, Man and Cybernetics, 2003)
The purpose of this paper is to find characteristics of the body and physiological response to visual simulation of rolling from the standpoint of our thinking. There is a difference of unconscious response to the ship's environment between the human navigator and inexperienced persons, and we measured the subject's center of gravity, R-R interval and nasal temperature to evaluate our thinking.